The enforcement of EU law the role of the European Commission - Andersen, Stine (Oxford : Oxford University Press, 2013)
Examining the European Commission's current range of practices for exercising control over the meaning and implementation of EU law, this book provides a comprehensive analysis of centralised EU enforcement. It describes the different practices available analysing their effectiveness and discussing the Commission's role in ensuring compliance.
Series from CIP print record.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Effectiveness and validity of law -- European Union countries; International and municipal law -- European Union countries; European Commission